Multi-particulate Drug Delivery Systems of Methylphenidate Hydrochloride: Optimization of Formulation Using Statistical Experimental Design - Mukkala, Bala Vishnu Priya (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The objective of the present investigation was to develop a multiparticulate modified release system of methylphenidate hydrochloride (HCl) generating biphasic release profile from single core. Materials and Methods: Wurster (bottom spray fluid bed coating) process was employed to develop extended release (ER) pellets of methylphenidate HCl. Impact of various formulation variables was assessed using statistical interpretation such as analysis of variance. A 32 (two factor, three level) factorial design was employed to study the effect of independent variables (ER polymer [Eudragit RSPO/ Eudragit RLPO/Ethocel] concentration and plasticizer concentration), on dependent variables (drug release at 3rd and 8th h). Optimization was done by fitting experimental data to the software program (Design Expert). The design space for formulation variables (ER polymer concentration and plasticizer concentration) and its influence on drug release was developed. Results and Discussion: Fabricated pellets were characterized for various physicochemical parameters. In vitro release data observed from the optimized formulation was fitted into various kinetic equations. The optimized formulation showed desired drug release at both 3rd and 8th h as 60.33% Â± 0.58% and 93.33% Â± 0.58%, respectively. Capsules showed an initial burst release preceding a more gradual ER phase following first order kinetics and Fickian diffusion process. Conclusion: Methylphenidate HCl ER pellets were successfully developed by employing bottom spray fluid bed coating (Wurster) technique. The factorial experimental design facilitated the formulation and optimization of modified drug delivery system of methylphenidate HCl.